Sol–gel based calcium phosphates coatings deposited on binary Ti–Mo alloys modified by laser beam irradiation for biomaterial/clinical applications - dos Santos, Marcio Luiz; dos Santos Riccardi, Carla [UNESP]; de Almeida Filho, Edson [UNESP]; Guastaldi, Antonio C. [UNESP] (Springer Nature, 2018)
Ti-15Mo alloy samples were irradiated by pulsed Yb: YAG laser beam under air and atmospheric pressure. Calcium phosphate coatings were deposited on the irradiated surfaces by the sol–gel method. The sol was prepared from the precursors Ca (NO3)2.4H2 O and H3 PO4. The modified surfaces were submitted to heat treatment conditions at 350 and 600 °C. The results showed that the two conditions established have a sufficient energy to promote ablation on the laser beam irradiated surfaces. Likewise, it has been demonstrated the processes of fusion and fast solidification from the laser beam irradiation, under ambient atmosphere, inducing the formation of stoichiometric TiO2 and non-stoichiometric titanium oxides, including Ti3O5, TiO, Ti3O and Ti6O with different oxide percentages depending on the fluency used. Besides that, laser modification has allowed a clean and reproducible process, providing no traces of contamination, an important feature for clinical applications. The physico-chemical and morphological properties indicated the formation of a mixture of phases: calcium pyrophosphate, hydroxyapatite and β-TCP for the procedure (PA: calcination temperature), whereas HA (hydroxyapatite) and β-TCP (tricalcium phosphate) were obtained by the procedure (PB: calcination temperature). Therefore, it was possible to obtain a Ti-15Mo alloy surface consisted on calcium phosphate ceramics of biological interest using the procedure (PB). Thus, the laser beam irradiation associated to bioactive coatings of calcium phosphates of biological interest have shown to be promising and economically feasible for use in dental and orthopedic implants. [Figure not available: see fulltext.].